1971
DOI: 10.1111/j.1365-2621.1971.tb04038.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Types and Levels of Fat and Rates and Temperatures of Comminution on the Processing and Characteristics of Frankfurters

Abstract: — Frankfurter emulsions containing either 25% or 35% beef fat, pork fat, or cottonseed oil were prepared by comminuting at 1500, 2500, or 5000 rpm to temperatures ranging from 45°–85°F. Data were obtained on the viscosities of the emulsions; except for initially high viscosities for which unmelted fat was responsible, the viscosities of emulsions containing the fats, or oil, were similar: viscosities tended to decrease with increasing time and temperature of chopping. The frankfurters were stuffed, smoked, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

1972
1972
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 2 publications
4
18
0
1
Order By: Relevance
“…Townsend et al (1971) suggested that emulsions containing beef fat should be comminuted to 65°-75°F. However, since the taste panel found no differences in tenderness in any of the combinations, except for beef alone, their lower scores for tenderness in this case can be taken as being undesirable because of the low values for overall acceptability.…”
Section: Series 1 Taste Panel Results As Shown Inmentioning
confidence: 99%
“…Townsend et al (1971) suggested that emulsions containing beef fat should be comminuted to 65°-75°F. However, since the taste panel found no differences in tenderness in any of the combinations, except for beef alone, their lower scores for tenderness in this case can be taken as being undesirable because of the low values for overall acceptability.…”
Section: Series 1 Taste Panel Results As Shown Inmentioning
confidence: 99%
“…Ranges of processing loss (including samples made with vegetable and marine oils) between 10 and 20% have been reported in the formulation of frankfurters with improved fat content Paneras & Bloukas, 1994). It has generally been reported that frankfurters prepared with vegetable oils have higher cooking losses than those prepared with animal fat (Ambrosiadis, Vareltzis, & Georgakis, 1996;Paneras & Bloukas, 1994;Park, Rhee, Keeton, & Rhee, 1989;Townsend, Ackerman, Witnauer, Palm, & Swift, 1971), but it has also been reported that cooking loss in meat batters decreased when animal fat was replaced by vegetable oils, and this effect was affected by the type of oil (Youssef & Barbut, 2011). It has also been reported that the cooking loss of frankfurters was not affected by the type of fat (pork or beef fat or vegetable oils) used in the formulation (Alvarez et al, 2011;Delgado-Pando, Cofrades, Ruiz-Capillas, Solas, et al, 2010a;Marquez, Ahmed, West, & Johnson, 1989).…”
Section: Processing Loss Purge Loss and Ph Determinationmentioning
confidence: 98%
“…However, the use of this pork fat in cooked sausage manufacture created stability problems in the batter (Shackelford et al, 1990(Shackelford et al, , 1991. Another alternative is to replace animal fat in products with vegetable oils rich in polyunsaturated fatty acids (Townsend et al, 1971;Whiting, 1987;Park et al, 1989;Hammer, 1991Hammer, , 1992.…”
Section: Introductionmentioning
confidence: 97%